NUCLEAR EDUCATION IN MEPHI - N. S. BARBASHINA; N. I. GERASKIN; G. V. TIKHOMIROV (Высшее образование в России)
The article highlights the milestones of the formation and the current state of nuclear education at National Research Nuclear University MEPhI. The authors dwell on the activities of the Institute of nuclear physics and engineering, which concentrates the training of the experts for Rosatom State Corporation. Thirty training programs now include all the levels of nuclear education (Bachelor’s Degree, Master’s degree, specialists’ courses, postgraduate and doctoral training).